2022
DOI: 10.1155/2022/5031806
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Prescribed Fire on Tick Spread and Propagation in a Spatial Setting

Abstract: Lyme disease is one of the most prominent tick-borne diseases in the United States, and prevalence of the disease has been steadily increasing over the past several decades due to a number of factors, including climate change. Methods for control of the disease have been considered, one of which is prescribed burning. In this paper, the effects of prescribed burns on the abundance of ticks present in a spatial domain are assessed. A spatial stage-structured tick-host model with an impulsive differential equati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 38 publications
6
27
0
Order By: Relevance
“…One of the main findings of this study was that yearly high-intensity fires were significantly more effective than yearly low-intensity fires. This strategy was also found to slow down the establishment of ticks in new areas [ 59 ]. Conversely, another study conducted in West Central Illinois found that the number of ticks collected at all life stages did not differ among burn treatments, which indicates the limited effect of low-intensity burning.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main findings of this study was that yearly high-intensity fires were significantly more effective than yearly low-intensity fires. This strategy was also found to slow down the establishment of ticks in new areas [ 59 ]. Conversely, another study conducted in West Central Illinois found that the number of ticks collected at all life stages did not differ among burn treatments, which indicates the limited effect of low-intensity burning.…”
Section: Resultsmentioning
confidence: 99%
“…al. [25] extended the model from [24] to a system of partial differential equations in order to determine how the effects of a spatial setting alter the effectiveness of prescribed burns. There, we found that a crucial determinant of the effectiveness of a prescribed burn was the size of the burn being performed.…”
Section: Discussionmentioning
confidence: 99%
“…We also see that few infectious questing adult ticks are able to survive the burns, further indicating that timing a burn during times of the year when this life stage is most active may be effective at further slowing the establishment of these ticks. Eradication of ticks from an area using prescribed burning alone likely is not possible [25], thus additional control measures should be implemented in conjunction with prescribed burning if the goal is eradication of ticks. Four prescribed burns is an unsustainable number to perform on an annual basis, but it is extremely effective for an initial reduction in tick populations in both endemic and invasion scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations